Ảnh hưởng của giới tính nhân sự quản lý cấp cao đến tốc độ điều chỉnh cấu trúc vốn của doanh nghiệp - Nguyễn Bá , Phong; Nguyễn Văn , Phong; Nguyễn Thị Mỹ , Phương; Đặng Thị Thanh, Trúc; Trần Quốc , Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
This paper investigates how top managers’ gender affects the adjustment speed of capital structure. With a sample of 599 firms listed in the Vietnamese stock market, the authors find that firms with female CEOs and a higher proportion of female in board members have higher adjustment speed of capital structure. Besides, our additional analysis shows that this relationship is stronger in small firms.
Keywords: Gender; CEO; Board of directors; Capital structure adjustment; Capital structure; Vietnam